Peran Camat dalam Melaksanakan Fungsi Pembinaan dan Pengawasan Terhadap Pengelolaan Keuangan Desa - Paulus Kristianus Nggaa (Journal of Social and Policy Issues, 2022)
This paper seeks to find answers two big questions in village financial management, namely: first, what is the role of the sub-district head in carrying out the function of fostering and supervising village financial management? Second, how to understand the substance of the village financial management process? The district head carries out a functional role consisting of facilitation, coordination, and recommendations. One of the facilitation functions is coaching and supervising village financial management. The Real conditions illustrate that there are still many problems encountered due to the chaotic process of village financial management. This research is qualitative by using the descriptive method. The author collects data through interviews were conducted with related parties such as the sub-district head, head of the government section, the village head, village finance head, and village community members. The results of the study illustrate that the role of the sub-district head is still not optimal, because the space provided by the district is only administratively limited to conducting pre-evaluation activities on the 3 mandatory documents that must be owned by the village and controlling development activities that occur in the village. village in the survey and verification stage. For this reason, it is necessary to make significant changes to overcome it. Concrete steps that can be taken are by simplifying work procedures through an information technology approach and involving the sub-district head in the entire village financial management process starting from the planning and budgeting stages, implementation and administration as well as reporting and accountability.